2018
DOI: 10.1155/2018/4050714
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Uncover the Molecular Mechanisms of Herbal Formula Ban‐Xia‐Xie‐Xin‐Tang

Abstract: Ban-Xia-Xie-Xin-Tang (BXXXT) is a classical formula from Shang-Han-Lun which is one of the earliest books of TCM clinical practice. In this work, we investigated the therapeutic mechanisms of BXXXT for the treatment of multiple diseases using a network pharmacology approach. Here three BXXXT representative diseases (colitis, diabetes mellitus, and gastric cancer) were discussed, and we focus on in silico methods that integrate drug-likeness screening, target prioritizing, and multilayer network extending. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 96 publications
0
47
0
Order By: Relevance
“…In addition, clinical experiments have also confirmed that a variety of compound Traditional Chinese formulas contains Scutellaria and Coptidis such as Gegenqinlian decoction and Pinellia-Xiexin decoction can significantly improve the clinical symptoms and serum biochemical indexes of T2DM, [ 15 , 16 ] achieving the goal of blood glucose control and improve the patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical experiments have also confirmed that a variety of compound Traditional Chinese formulas contains Scutellaria and Coptidis such as Gegenqinlian decoction and Pinellia-Xiexin decoction can significantly improve the clinical symptoms and serum biochemical indexes of T2DM, [ 15 , 16 ] achieving the goal of blood glucose control and improve the patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Use of Ban-Xia-Xie-Xin-Tang was found to lessen the risk of developing CRC in patients with type 2 diabetes. One possible mechanism may involve the anti-inflammatory properties of Ban-Xia-Xie-Xin-Tang,35 36 which is often used to treat various digestive inflammations, like colitis, esophagitis and gastritis 37. Chronic inflammation of the bowel has been hypothesized as the most important mechanism driving CRC onset 38…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targeted drugs for OA have been a great challenge for the development of pharmaceutical formulations [26]. Therefore, it represents a highly attractive tool owing to its potential to investigate complex relationships between chemicals and target proteins [27].…”
Section: Discussionmentioning
confidence: 99%